Measuring and valuing spillover effects in caregivers and families: A scoping review - Tho T. H. Dang; Angeli Tabinga; Hannah Beilby; Natalie Barker; Luke R. Johnson; Haitham Tuffaha; Luke B. Connelly; Angela M. Maguire (PLoS ONE, 2026)
Objectives As healthcare increasingly relies on informal care for chronic and complex conditions, economic evaluations have expanded beyond patient outcomes to consider spillover effects on caregivers and families. This scoping review aimed to map existing measures and methods for assessing these effects and to identify potential mechanisms, mediators, and moderators to inform future survey design. Methods We conducted a comprehensive search of four databases (PubMed, APA PsycInfo, CINAHL Complete, and EconLit) for English-language studies published from 2017 to 2025, including quantitative, qualitative, and mixed-methods research reporting monetary or non-monetary spillovers. Screening and study selection followed the Participants, Concept, Context framework and were reported according to PRISMA-ScR guidelines. Results A total of 141 studies met the inclusion criteria. Incorporating caregiver and family spillovers could meaningfully alter cost-effectiveness estimates, but this practice remained inconsistent due to limited data and methodological variability. Comprehensive assessment of spillover effects benefited from combining generic, caregiver-specific, and disease-specific tools to capture both perceived and measurable impacts. Valuation of societal and economic spillovers, including informal care time, costs, productivity loss, and wellbeing impact, was influenced by methodological choices, caregiver and patient characteristics, and caregiving context, highlighting the need for flexible, context-sensitive approaches. Caregiver outcomes reflected the interplay of mediating factors (psychological, social, relational) and moderating influences (coping, spirituality, support systems, caregiving intensity). Subjective caregiver burden was pivotal, shaping and conditioning the effects of caregiving stressors on wellbeing. Conclusion Establishing consensus on best-practice approaches for incorporating spillover effects in economic evaluations is needed to accurately quantify their impact on caregivers and families and to inform interventions that reduce caregiver burden.